2017
DOI: 10.1038/pr.2017.299
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of death in infants with probable serious bacterial infection

Abstract: BackgroundBacterial infections account for a significant proportion of neonatal and infant mortality globally. We aimed to identify predictors of death in infants with probable serious bacterial infection (PSBI) defined as signs/symptoms of possible serious bacterial infection along with baseline C-reactive protein (CRP) ≥12 mg/l.MethodsWe did a secondary analysis using the data collected from 700 infants with PSBI who participated in a randomized controlled trial in India in which zinc or placebo was given in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…This finding corresponds to the 7-day findings of Dire Dawa (23) and Central Gondar (16). This is also comparable to the findings of earlier studies conducted in Uganda (31) and India (32), which reported median times to recovery for septic neonates of 4.5 and 5.5 days, respectively. These studies shared certain characteristics with the current investigation, such as being conducted on newborns admitted to public hospitals, having a neonate age limit of 0-28 days, having similar sample sizes, and considering clinically confirmed cases.…”
Section: Discussionsupporting
confidence: 90%
“…This finding corresponds to the 7-day findings of Dire Dawa (23) and Central Gondar (16). This is also comparable to the findings of earlier studies conducted in Uganda (31) and India (32), which reported median times to recovery for septic neonates of 4.5 and 5.5 days, respectively. These studies shared certain characteristics with the current investigation, such as being conducted on newborns admitted to public hospitals, having a neonate age limit of 0-28 days, having similar sample sizes, and considering clinically confirmed cases.…”
Section: Discussionsupporting
confidence: 90%
“…It is usually used as a useful predictor for infection, or even death, in infants with a probable serious bacterial infection. 26,27 Our results showed that either CRP or WBC could discriminate infants with CAP, but the sensitivities of these two markers for the diagnosis of CAP were poor, although CRP showed higher specificity. The high specificity for CRP may be due to the presence of upregulated serum Pin1.…”
Section: Discussionmentioning
confidence: 67%
“…Several, low-risk criteria and clinical prediction models have been developed to screen for serious bacterial infections in febrile young infants [10,11]. Although these diagnostic tools have expedited clinicians' decision making and helped to improve the use of resources in pediatric acute care [12,13], clinicians may still misdiagnose serious viral infections if they rely only on methods used to diagnose bacterial infections [14,15].…”
Section: Introductionmentioning
confidence: 99%